1997
DOI: 10.1007/s005920050059
|View full text |Cite
|
Sign up to set email alerts
|

Release of glucagon-like peptide-1 (GLP-1) by carbohydrates in the perfused rat ileum

Abstract: The effect of various carbohydrates on glucagon-like peptide-1 (GLP-1) release was studied in the in vivo perfused rat ileum. GLP-1 concentrations in the mesenteric venous effluent increased significantly after luminal perfusion with substrates of a sodium/glucose co-transporter (D-glucose, D-galactose, methyl-alpha D-glucoside, and 3-O-methyl-D-glucose). D-Fructose induced a sodium-independent release of GLP-1. Carbohydrates like 2-deoxy-D-glucose and N-acetyl-D-glucosamine, which are not substrates of a lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 15 publications
6
61
1
1
Order By: Relevance
“…The idea that low concentrations of glucose trigger GLP-1 release through metabolism and K ATP channel closure seems contrary to results obtained using perfused rat ileum, which showed that some nonmetabolizable glucose analogues also stimulate GLP-1 release (35). The ileal perfusion experiments, however, tested substrates at much higher concentrations (ϳ250 mmol/l) than those used in the current study, and might stimulate secretion by an alternative mechanism.…”
Section: Discussioncontrasting
confidence: 91%
“…The idea that low concentrations of glucose trigger GLP-1 release through metabolism and K ATP channel closure seems contrary to results obtained using perfused rat ileum, which showed that some nonmetabolizable glucose analogues also stimulate GLP-1 release (35). The ileal perfusion experiments, however, tested substrates at much higher concentrations (ϳ250 mmol/l) than those used in the current study, and might stimulate secretion by an alternative mechanism.…”
Section: Discussioncontrasting
confidence: 91%
“…It should also be noted that major differences between species are evident with regards to incretin hormone release. For example, fructose stimulates the release of GLP-1 in rats (38) and humans (36) but not in dogs (41).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies examining the sugar specificity of gut peptide responses in the intact intestine concluded that sugar absorption was important for hormone stimulation. Glucose-triggered secretion exhibited a requirement for luminal Na + ions and was mimicked by metabolisable as well as non-metabolisable substrates of the brush border monosaccharide transporter system (40)(41)(42) . The results indicated that glucose uptake rather than metabolism was critical for GLP-1 and GIP secretion.…”
Section: Carbohydrate Sensingmentioning
confidence: 99%
“…Consistent with this idea, intestinal GLP-1 content and secretion were found to be impaired in GLUT2 knockout mice (48) . The observed small GLP-1 response to oral fructose might also be attributable to metabolism (41) , as apical fructose uptake is mediated by GLUT5, whose activity does not generate an electrical signal.…”
Section: Carbohydrate Sensingmentioning
confidence: 99%